PENGARUH KONDISI KEUANGAN PERUSAHAAN, UKURAN PERUSAHAAN, OPINION SHOPPING, KUALITAS AUDIT, AUDIT CLIENT TENURE, DEBT DEFAULT DAN AUDIT LAG TERHADAP PENERIMAANOPINI AUDIT GOING CONCERN (Studi Empiris Pada PerusahaanManufaktur Yang Terdaftar di BEI Tahun 20 - Riza Safitri; Desmiyawati '; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The financial statements are an important part of this due to become the main information required by potential investors. Nowdays, auditor’s responsibility to disclose the information about the entity was not only things revealed in the financial statement, but also must be disclose information such us the excistence and contuinity of an entity. Auditor was expected to not only examine the financial statement, but also can predict and appraise entity’s ablity to continues his existence.This research’s goal was to examine the effect of financial condition, firm size, opinion shopping, audit quality, audit client tenure,debt default and audit lag to the acceptance of going concern audit opinion. The samples of this research were manufacturing companies that listed in Indonesia Stock Exchange on period 2010-2014.Population of this research was 131 companies. Samples of this research were 12 companies selected by purposive sampling method, with 5 years observationperiod. The data was analiyzed by logistic regression method.The result showed that opinion shopping issignificantly affect the going concern audit opinion. Whereas, of financial condition, firm sizeaudit quality, audit client tenure,debt default and audit lag have no affect with the going concern audit opinion.Keyword: going concern,opinion shopping, audit quality, debt default, audit lag.